Organic structural properties of kerogen as predictors of source rock type and hydrocarbon potential. (15th November 2016) - Longbottom, Todd L.; Hockaday, William C.; Boling, Kenneth S.; Li, Gaoyuan; Letourmy, Yohan; Dong, Hailiang; Dworkin, Stephen I.
Highlights: Immature kerogens of types I–III were analyzed by 13 C NMR and Rock-Eval pyrolysis. An NMR-based technique reliably delineated kerogen types. Structure-catagenic relationships described hydrocarbon generation during pyrolysis. Abstract: This study improves upon previously identified correlations between the chemical structure of kerogen and potential hydrocarbon (oil and gas) yields assayed by Rock-Eval pyrolysis. We propose a quantitative structure-catagenesis relationship that predicts the hydrocarbon generation potential of source rocks and of lacustrine, marine, and terrestrial origin (types I, II, and humic coals). We used one-dimensional solid-state 13 C Nuclear Magnetic Resonance ( 13 C NMR) spectroscopy with 1 H spectral editing to determine the abundance of carbon functional groups, including non-protonated and mobile groups. An NMR-based van Krevelen analysis readily separated the kerogen types. Single regression matrices of NMR-based structure parameters against Rock-Eval hydrocarbon yield revealed distinct dynamics of the kerogen types upon pyrolysis. Multiple regression showed that alkyl, oxygen-substituted alkyl, and carbonyl groups were strong contributors to hydrocarbon production, while oxygen-substituted aromatic carbons were strongly counterproductive. Catagenetic relationships established for kerogen provide insight into kerogen structure evolution upon pyrolysis, and can more closely constrain the mechanisms of hydrocarbon generation for use in sedimentary basin modeling.